Neural substrate differences in language networks and associated language-related behavioral impairments in children with TBI: A preliminary fMRI investigation. - Karunanayaka PR; Holland SK; Altaye M; Jones BV; Michaud LJ; Walz NC; Wade SL (NeuroRehabilitation, 2007)
The present study examined whether functional MRI (fMRI) can identify changes in the neural substrates of language in young children following traumatic brain injury (TBI). Eight children with TBI (F/M=3/5, age (Mean ± SD)=7.98 ± 1 years, range = 6-9 years) and a comparison group of nine children with orthopedic injuries (OI) (F/M=4/5, age (Mean ± SD)=7.4 ± 1 years, range=6-9 years) participated in an fMRI study of covert verb generation (VG). Results revealed significantly different BOLD signal activation in perisylvian language areas between the groups, after accounting for potential confounders such as verbal fluency and executive function. We also found significant associations between the BOLD signal activation and performance on language-specific neuropsychological tests (NEPSY verbal fluency score, Verbal IQ) and Glasgow Coma Scale (GCS) score. This study suggests that children with TBI have significantly different brain activation patterns in language circuitry compared to children with orthopedic injuries. Although we found clear differences in brain activation between the two groups, conventional MR images showed no evidence of structural abnormalities in five of eight children with TBI. Our study demonstrates the feasibility and potential utility of fMRI as a means of quantifying changes associated with language deficits in future pediatric TBI studies.